Gender Equality in Sustainable Development Goals: Some Reflections from Nepal - Khanal, Shushila Devi (Journey for Sustainable Development and Peace Journal, 2023)
The paper examines the connection between gender equality and the Sustainable Development Goals (SDGs). It explores how gender equality is essential for achieving sustainable development and addresses the specific challenges and progress made in Nepal towards SDGs. Methodologically, the paper is based on the review and synthesis of secondary sources of information by explorative method. This paper mainly discusses the social, economic, environmental, and partnership aspects of SDGs in relation to gender equality and their contribution to human well-being and justice. It emphasizes the need for comprehensive and coordinated efforts to address gender disparities, promote women's empowerment, and ensure the active participation of women and girls in decision-making processes. Finally, the paper concludes by discussing the importance of integrating gender equality into policies, programs, and strategies aimed at achieving sustainable development in Nepal.